Kesulitan Belajar Bahasa Indonesia oleh Pemelajar BIPA Level Dasar (BIPA 1) di Hanoi Vietnam - Eko Widianto (Jurnal Bahasa Indonesia bagi Penutur Asing, 2021)
BIPA students in Hanoi, Vietnam have unique characteristics. For this reason, this study aims to reveal the learning difficulties of BIPA students at the basic level. This research is a case study that describes the difficulties of BIPA students in Hanoi, Vietnam in learning Indonesian language and culture. The research was conducted with an autoethnographic approach. The data of this research are fragments of speech and learning outcomes of BIPA students. This is generated from data sources in speech and discourse in BIPA learning in the classroom. The data is generated from the natural observation process. The data was presented informally. These difficulties become their unique and distinctive character. This can be used as a basis for preparing teaching materials and learning processes. In general, some difficulties are found at the phonological, morphological, syntactic, and discourse levels. For example, the word [rusak] becomes [lusak], [ramai] becomes [zamai], and [rajin] becomes [lajin]. This is influenced by the habits of Vietnamese speakers who often pronounce the sound [r] at the beginning of the word to become [z], such as [rau] to [zau] which means 'vegetable', [rεt] becomes [zεt] which means 'very'. The difficulty of BIPA students is generally influenced by their first or second language, namely Vietnamese and English. Therefore, these difficulties need to be identified and grouped as recommendations for learning BIPA in Hanoi, Vietnam in the next period.